PEMBERDAYAAN USAHA KECIL MENENGAH DAN KOPERASI SEBAGAI PENGGERAK PERTUMBUHAN EKONOMI - Wibowo, Edi (Universitas Slamet Riyadi, 2011)
ABSTRACT Micro, Small and Medium Enterprises (SMEs) are the largest group of economic actors in the Indonesian economy and proved to be the national economic safety valve in times of crisis, as well as being dynamist economic growth after economic crisis. Besides being the largest business sector contribution to national development, SMEs are also creating substantial employment opportunities for workers in the country, so it is helping to reduce unemployment. One key to the success of micro, small and medium enterprises is the availability of a clear market for the products of SMEs. Meanwhile, the fundamental weaknesses faced by SMEs in the field of marketing is a low market orientation, weak in a complex and sharp competition and inadequate marketing infrastructure. Faced with an increasingly open market mechanisms and competitive, market control is a prerequisite to improve competitiveness. Therefore, the role of government is needed in encouraging the success of SMEs to expand market access. Keywords: empowerment, micro small and medium enterprises, economic growth Â